Putative Role of an ABC Efflux System in Aliarcobacter butzleri Resistance and Virulence - Inês Martins; Cristiana Mateus; Fernanda Domingues; Mónica Oleastro; Susana Ferreira (MDPI AG, 2023)
Aliarcobacter butzleri is considered a ubiquitous microorganism and emergent pathogen, for which increasing rates of multidrug resistance have been described. In line with this, the present work aimed to evaluate for the first time the contribution of an ABC efflux system, the YbhFSR, in the resistance and virulence of this bacterium. Following the in silico characterization of the YbhFSR transporter, a mutant strain was constructed by inactivating the gene responsible for ATP-binding. After ensuring that the mutation did not have an impact on bacterial growth, the resistance profile of parental and mutant strains to different antimicrobial agents was evaluated. The results suggest that the efflux pump may influence the resistance to benzalkonium chloride, ethidium bromide, and cadmium, and several other compounds were identified as potential substrates. Regarding the evaluation of the accumulation of ethidium bromide, a slight increase was observed for the mutant strain, demonstrating a potential role of the YbhFSR efflux pump in the extrusion of toxic compounds from A. butzleri. Subsequently, the role of this efflux pump on the A. butzleri known virulence properties was evaluated, but no difference was seen among mutant and parental strains for the motility, biofilm formation ability, susceptibility to oxidative stress, or the ability to adhere and invade Caco-2 cells. However, in contrast to the parental strain, the mutant strain showed a resistance to human serum. Overall, the results support the role of efflux pumps in A. butzleri resistance to antimicrobials, highlighting the particular role of the YbhFSR system.